2007
DOI: 10.1292/jvms.69.253
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte Apoptosis and Decrease of Glycosaminoglycan in Cranial Cruciate Ligament Insertion after Resection in Rabbits

Abstract: ABSTRACT. We examined time-dependent histological changes of the calcified fibrocartilage area in a tibial cranial cruciate ligament (CCL) insertion after ligament resection in rabbits. The animals were divided into two groups: those undergoing CCL substance resection in the right stifle (resected group) and those receiving the same operation without CCL resection in the left stifle (sham operated group). Five animals were euthanized with deep anaesthesia at four time periods (1, 2, 4 and 6 weeks), and Haemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 25 publications
8
22
0
Order By: Relevance
“…In this study, the chondrocyte apoptosis rate in normal insertions was similar to those in previous reports of calcified cartilage layer in ACL insertion of rabbits [5] and articular cartilage of mice and rats [11]. The chondrocyte apoptosis rate in normal insertions was lower than that in the ruptured ACL group.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the chondrocyte apoptosis rate in normal insertions was similar to those in previous reports of calcified cartilage layer in ACL insertion of rabbits [5] and articular cartilage of mice and rats [11]. The chondrocyte apoptosis rate in normal insertions was lower than that in the ruptured ACL group.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we reported that histological degenerative changes of the cartilage layer due to chondrocyte apoptosis in a ruptured ACL tibial insertion progress with time, particularly in the first 2 months [4]. We also reported that 2 and 4 weeks after ACL resection in rabbits, the percentages of TUNEL-positive chondrocytes were significantly higher than those in the shamoperated group, and histological changes occurred 6 weeks after the resection [5]. In our present study, we observed that approximately 30% of chondrocytes were apoptotic in ruptured ACL insertions and approximately 10% of chondrocytes in normal insertions.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…These studies reported that the increased apoptosis chondral tissue was related to chondral degeneration. 19,[22][23][24][25] This study has some limitations. Six weeks of follow-up is a short-term period to observe a longacting drug such as ZA.…”
Section: Discussionmentioning
confidence: 95%